2018
DOI: 10.1177/0022034518759957
|View full text |Cite
|
Sign up to set email alerts
|

Transillumination and HDR Imaging for Proximal Caries Detection

Abstract: The purpose of this study was to develop an in vitro model for the validation of near-infrared transillumination (NIRT) for proximal caries detection, to enhance NIRT with high-dynamic-range imaging (HDRI), and to compare both methods, using micro-computed tomography (µCT) as a reference standard. Both proximal surfaces of 53 healthy or decayed permanent human teeth were examined using the Diagnocam (DC) (KaVo) and NIRT with HDRI (NIRT-HDRI). NIRT was combined with HDRI to improve the diagnostic performance by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 25 publications
0
10
0
3
Order By: Relevance
“…Images were captured using the VistaSoft software and were exported as Portable Network Graphics files. The proximal surfaces were evaluated following an existing classification of NIR transillumination according to the following criteria: sound (code 0); caries limited to enamel (code 1); caries with a single point of contact to the enamel–dentin junction (code 2); caries with extensive contact to the enamel–dentin junction (code 3); and caries visible in dentin (code 4) .…”
Section: Methodsmentioning
confidence: 99%
“…Images were captured using the VistaSoft software and were exported as Portable Network Graphics files. The proximal surfaces were evaluated following an existing classification of NIR transillumination according to the following criteria: sound (code 0); caries limited to enamel (code 1); caries with a single point of contact to the enamel–dentin junction (code 2); caries with extensive contact to the enamel–dentin junction (code 3); and caries visible in dentin (code 4) .…”
Section: Methodsmentioning
confidence: 99%
“…22 However, the significant heterogeneity in the study designs and the reference standards make it difficult to affirm that NIRLT could substitute X-rays in the auxiliary diagnosis of carious lesions. Furthermore, among these studies, an in-vitro model cannot completely simulate the intra-oral condition whereas some in-vivo experiments used visual inspection or cavities opening as a reference standard, [16][17][18][19][20][21][22][23][24][25] which cannot be used as a gold standard to accurately assess the sensitivity and specificity of DC. As Macey et al reported, high-quality studies for DC could still be useful becausetheir true effect on the dental examination does not currently seem to have been explored.…”
Section: Introductionmentioning
confidence: 99%
“…This increase in fluorescence is mainly due to a bacterial photosensitive pigment present in caries tissue, but it could also be contributed by other factors related to oral hygiene. The FOTI/DIFOTI, NIRT, and LF methods have all been commercialized in dentistry, and their caries detection sensitivity/specificity is currently under examination [19]. Nowadays, the LF method is perhaps the most advanced radiation-free method available to enhance early identification of caries and to follow their development through regular successive examinations.…”
Section: Introductionmentioning
confidence: 99%